2010
DOI: 10.1371/journal.pone.0015903
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Fever: The Potential Relationship with Prognosis in Node Negative Breast Cancer Patients

Abstract: BackgroundPostoperative fever may serve as an indirect sign to reflect the alterations of the host milieu caused by surgery. It still remains open to investigation whether postoperative fever has a bearing on prognosis in patients with lymph node negative breast cancers.MethodsWe performed a retrospective study of 883 female unilateral patients with lymph node negative breast cancer. Fever was defined as an oral temperature ≥38 in one week postoperation. Survival curves were performed with Kaplan-Meier method,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…Similarly, we demonstrated that those who had a complication after immediate breast reconstructive surgery were more likely to develop breast cancer recurrence, both locally and distantly [23]. Yan et al [24] discovered that patients who have a fever in the post-operative period are more likely to develop breast cancer recurrence. Post-operative fever may indirectly reflect changes in host systemic factors.…”
Section: Breast Cancersupporting
confidence: 63%
“…Similarly, we demonstrated that those who had a complication after immediate breast reconstructive surgery were more likely to develop breast cancer recurrence, both locally and distantly [23]. Yan et al [24] discovered that patients who have a fever in the post-operative period are more likely to develop breast cancer recurrence. Post-operative fever may indirectly reflect changes in host systemic factors.…”
Section: Breast Cancersupporting
confidence: 63%
“…Similar evidence in breast cancer is limited; however, one study has suggested that delayed wound healing is associated with an increased rate of systemic recurrence after primary breast cancer surgery. In addition, patients who experience fever in the postoperative period are also more likely to develop breast cancer recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative fever has been independently associated with increased recurrence (Relative Risk 1.89, 95% CI 1.02 to 3.52) 36. A possible mechanism is that fever-related host inflammatory response reduces eradication of neoplastic cells.…”
Section: Surgery Pain Stress Response and Cancer Recurrencementioning
confidence: 99%